O inferno é aqui: a estética grotesca da banda cicuta e a representação poética transmidiática na obra viver até morrer - Felipe, Frederico Carvalho (2015)
The objective of this work is to contribute to studies about the grotesque aesthetic in rock'n'roll and the use of different media platforms as a means of poetic styling and creating new narratives converge to Viver até Morrer. The grotesque as a visual representation of the anxieties and contradictions of an age full of constant daily shocks that the people is exposed challenge institutionalized social models through the aesthetics. The transmedia exhibition of the work provides an expansion of the fictional imaginary narratives through interconnections from different platforms and media languages such as animated film, the music video, comics and music.